การสอนแบบมอนเตสซอรี่ให้กับนักศึกษาสาขาวิชาการศึกษาปฐมวัย มหาวิทยาลัยสวนดุสิต: อดีต ปัจจุบัน อนาคต - นพคุณ อาจารย์ ดร.จุฬินฑิพา (Journal of Multidisciplinary in Social Sciences, 2019)
This article presents past, present and future information on teaching montessori method to early childhood students, Suan Dusit University. This article describes the connection of events during various periods of development of montessori instruction to early childhood education students. By presenting the history of teaching montessori method , teaching montessori method and students in the montessori system, this article links to the study of historical evidence on the teaching of montessori to early childhood students, Suan Dusit University and presents a method of teaching montessori teaching to students in the field of early childhood education, Suan Dusit University at present. This enables learners to engage in true learning through the creation of knowledge, study visit and practice. This article describes the future montessori course that students need to be able to apply the knowledge in their classroom in the future.